DISTRIBUSI PENDAPATAN PETANI EKS UPP TCSDP DI DESA SIALANG KAYU BATU KECAMATAN BUNUT KABUPATEN PELALAWAN - Indo Muharram Afdillah; Eliza Eliza; Shorea Khaswarina (Universitas Sebelas Maret, 2017)
Abstract: The Ex UPP TCSDP Farmers are the farmers who get the government assistance in agriculture in 1992.UPP TCSDP stands for Unit of ProjectImplementation of Tree Crop Smallholder Development Program which is thisprogram is the government assistance to plantation farmers (rubber, coconut,sugarcane) funded by World Bank by applying management mergers related totechnology, production and marketing, in 1998 is the last planting, so it is called Exof UPP TCSDP. This research aims to analyze the sources and the income structureand to observe the distribution and inequality of income of The Ex UPP TCSDPFarmer. This research took place in SialangKayuBatu Village, Bunut Sub-District,PelalawanDistrict. The results showed that the income source was divided into twoincome source from agricultural and non-agricultural. Total income from agricultural per year was Rp. 1.685.603.901 (89,95%), while total income from non-agriculturalper year was Rp. 188.400.000/year (10,05%). The highest income distribution was inthe Ex UPP TCSDP Farmers in the middle class as many as 9 farmers with totalproportion of income per year amount Rp. 769.422.455 (41,06%), while for the lowestincome proportion was the Ex UPP TCSDP Farmers in the lowest class as many as 9farmers with total proportion of income amount Rp. 409.293.513 (21,84%).The IndexValue of Gini Ratio was in low or mild inequality that equal to 0,20. It is indicatedthat, the income equalityof The Ex UPP TCSDP Farmer in SialangKayuBatu villageBunut Sub-District Pelalawan District was good. Abstrak : Petani Eks UPP TCSDP adalah petani yang mendapatkan bantuanpemerintah di bidang pertanian pada tahun 1992. UPP TCSDP merupakan singkatandari Unit Pelaksanaan Proyek Tree Crop Smallholder Development Program dimanaprogram ini berupa bantuan yang diberikan pemerintah kepada petani perkebunan(karet, kelapa, tebu) yang dibiayai oleh Bank Dunia dengan melaksanakanpenggabungan manajemen yang berkaitan dengan teknologi, proses produksi, danpemasaran, pada tahun 1998 merupakan tanam terakhir sehingga disebut Eks UPPTCSDP. Penelitian ini bertujuan untuk menganalisis sumber-sumber dan strukturpendapatan serta distribusi dan ketimpangan pendapatan petani Eks UPP TCSDPdiDesa Sialang Kayu Batu Kecamatan Bunut Kabupaten Pelalawan.. Penelitian denganmetode survey dan pengambilan responden secara simple random sampling. Hasilpenelitian menunjukkan bahwa sumber pendapatan ada duayaitu pendapatan dari pertanian dan non pertanian.Total pendapatan dari pertanian per tahun sebesar Rp.1.685.603.901(89,95%), sedangkan total pendapatan dari non pertanian sebesarRp.188.400.000 (10,05%). Distribusi pendapatan tertinggi terdapat pada petani EksUPP TCSDP golongan menengah sebanyak 9 orang dengan total proporsi jumlahpendapatan per tahun sebesar Rp.769.422.455 (41,06%), sedangkan untuk proporsipendapatan terendah sebanyak 9 orang dengan total proporsi jumlah pendapatan pertahun sebesar Rp. 409.293.513 (21,84%).Nilai Indeks Gini Ratio berada pada ketimpangan rendah atau ringan yaitu sebesar 0,20, artinya kemerataan pendapatan petani Eks UPP TCSDPdi Desa Sialang Kayu Batu Kecamatan Bunut Kabupaten Pelalawan tergolong baik.